Sacred Harmony: Exploring Pikukuh Tilu Philosophy in the Spiritual, Social, and Environmental Practices of the Baduy People - Frans H. M. Silalahi; Edi Purwanto (Pharos Journal of Theology)
This study explores Pikukuh Tilu, a fundamental philosophical belief system within the Baduy Tribe in Banten, Indonesia, and its role in shaping the community’s social, spiritual, and environmental practices. Rooted in the interconnectedness of God, humans, and nature, Pikukuh Tilu is a guiding principle that governs the Baduy people’s way of life, ensuring cultural continuity and ecological sustainability, particularly in relation to Sustainable Development Goals (SDGs) 11 (Sustainable Cities and Communities), 13 (Climate Action), and 15 (Life on Land). This research adopts a qualitative approach, utilizing ethnographic fieldwork, in-depth interviews, and participant observation to analyze the practical applications of Pikukuh Tilu in governance, rituals, and daily conduct. To provide a comprehensive theoretical framework, the study integrates perspectives from Structuralism, Functionalism, Local Wisdom, and Deep Ecology, offering a multidimensional understanding of how Pikukuh Tilu functions as both a belief system and a mechanism for cultural resilience. The findings reveal that Pikukuh Tilu is crucial in reinforcing social cohesion, moral values, and environmental ethics, enabling the Baduy people to maintain their traditional identity despite external pressures from modernization and globalization. Furthermore, the study highlights how Pikukuh Tilu embodies a sustainable indigenous knowledge system that aligns with contemporary environmental discourses on conservation and deep ecology. This research contributes to broader discussions in anthropology, cultural studies, and environmental philosophy, emphasizing the significance of indigenous belief systems in fostering sustainable living. By shedding light on the enduring relevance of Pikukuh Tilu, the study advocates for preserving Baduy’s cultural heritage. It offers insights into how traditional wisdom can inform modern ecological and social sustainability approaches.